Genome Characterisation of an Isoprene-Degrading Alcaligenes sp. Isolated from a Tropical Restored Forest - Uttarotai, Toungporn; Sutheeworapong, Sawannee; Crombie, Andrew T.; Murrell, J. Colin; Mhuantong, Wuttichai; Noirungsee, Nuttapol; Wangkarn, Sunanta; Bovonsombut, Sakunnee; McGenity, Terry J.; Chitov, Thararat (Biology (Basel, Switzerland), 2022)
Isoprene is a climate-active biogenic volatile organic compound (BVOC), emitted into the atmosphere in abundance, mainly from terrestrial plants. Soil is an important sink for isoprene due to its consumption by microbes. In this study, we report the ability of a soil bacterium to degrade isoprene. Strain 13f was isolated from soil beneath wild Himalayan cherry trees in a tropical restored forest. Based on phylogenomic analysis and an Average Nucleotide Identity score of >95%, it most probably belongs to the species Alcaligenes faecalis. Isoprene degradation by Alcaligenes sp. strain 13f was measured by using gas chromatography. When isoprene was supplied as the sole carbon and energy source at the concentration of 7.2 × 105 ppbv and 7.2 × 106 ppbv, 32.6% and 19.6% of isoprene was consumed after 18 days, respectively. Genome analysis of Alcaligenes sp. strain 13f revealed that the genes that are typically found as part of the isoprene monooxygenase gene cluster in other isoprene-degrading bacteria were absent. This discovery suggests that there may be alternative pathways for isoprene metabolism.